PERAN UNDANG – UNDANG NOMOR 10 TAHUN 2009 TENTANG KEPARIWISATAAN DALAM PERLINDUNGAN DAN PELESTARIAN OBJEK WISATA - I Wayan Paramarta Jaya; I Gede Putra Ariana (Kertha Negara : Journal Ilmu Hukum, 2014)
The paper is titled "The Role of Law - Law No. 10 Year 2009 on tourism andpreservation" By using normative research method of this paper describes how the role oflaw in the preservation of attractions. Indonesia is one of the world's tourist destination forits natural beauty. The natural beauty of this time has managed the business objectives forthe welfare of the community itself in accordance with Article 33 paragraph (3) of the 1945Constitution. The beauty is supposed to be protected and preserved for the purpose ofsustainable tourism development.